Empowering Digital Citizenship in Indonesia: Navigating Urgent Digital Literacy Challenges for Effective Digital Governance - Isabella Isabella; Alfitri Alfitri; Ardiyan Saptawan; Nengyanti Nengyanti; Tawakkal Baharuddin (Journal of Governance and Public Policy)
Digital literacy is a crucial skill and knowledge for modern society, yet the level of digital literacy in Indonesia remains inadequate. A substantial body of research has been conducted on digital literacy in Indonesia. However, there is a scarcity of studies that have focused specifically on digital literacy policies and their role in the development of digital governance in Indonesia. Accordingly, this research aims to address this gap by analyzing the development and implementation of Indonesia's digital literacy policy to support digital governance in Indonesia. This research employs a qualitative approach, utilizing online research methods (ORMs) and NVivo 12 Plus as an analytical tool. The findings of this study demonstrate that digital literacy is a crucial factor in ensuring citizens' active involvement in governance, the efficiency of public services, the growth of the digital economy, and the security of the digital environment. It is imperative that Indonesians possess robust digital literacy skills, as this will facilitate enhanced access to online services and facilitate the integration of society into the evolving digital democratization landscape. This condition has the potential to render Indonesia prepared and responsive to the advent of the digital age. However, the implementation of digital literacy policies is also confronted with a number of inhibiting factors, including gaps in access and infrastructure, economic and social challenges, a lack of education and training, a lack of research and data, a lack of engagement and coordination between parties, rapid technological change, and a regulatory framework that is not yet fully accommodating. Consequently, Indonesia requires adaptive policies to surmount these impediments and facilitate a more uniform increase in digital literacy. By examining the evolution and implementation of digital literacy policies in Indonesia, this study provides valuable insights for relevant stakeholders, enabling the formulation and implementation of more effective digital literacy policies.